An Unusual Case of Suspected Microvascular Angina in a Newborn. (17th October 2012) - Cataldo, Stefania; Annoni, Giuseppe Alberto; Fiocchi, Stefano; Mauri, Luigi Daniele; Corato, Alessandra; Vignati, Gabriele
Abstract : Myocardial ischemia in pediatric population is uncommon and usually due to congenital heart disease or extracardiac conditions leading to poor coronary perfusion. A 6-day-old newborn presented with respiratory distress and signs of heart failure. ECG, echocardiography, and laboratory results were consistent with myocardial ischemia. Coronary angiography was performed to exclude anomalous origin of coronary arteries, showing normal coronary artery origin and course. Thrombophilia and extra-cardiac causes were ruled out. Clinical conditions improved with mechanical ventilation and diuretics, enzyme levels lowered, repolarisation and systolic function abnormalities regressed, but ischemic electrocardiographic and echocardiographic signs still presented during intense crying. Becaues of suspicion of microvascular angina, therapy with ASA and beta-blocker was started. At 5 month followup, the baby was in good clinical condition and no more episodes were recorded. We believe it is an interesting case, as no similar cases have been recorded till now.